Acquisition and maintenance of medical expertise: a perspective from the expert-performance approach with deliberate practice - Ericsson, K Anders (Academic medicine, 2015)
As a part of a special collection in this issue of Academic Medicine, which is focused on mastery learning in medical education, this Perspective describes how the expert-performance approach with deliberate practice is consistent with many characteristics of mastery learning. Importantly, this Perspective also explains how the expert-performance approach provides a very different perspective on the acquisition of skill. Whereas traditional education with mastery learning focuses on having students attain an adequate level of performance that is based on goals set by the existing curricula, the expert-performance approach takes an empirical approach and first identifies the final goal of training-namely, reproducibly superior objective performance (superior patient outcomes) for individuals in particular medical specialties. Analyzing this superior complex performance reveals three types of mental representations that permit expert performers to plan, execute, and monitor their own performance. By reviewing research on medical performance and education, the author describes evidence for these representations and their development within the expert-performance framework. He uses the research to generate suggestions for improved training of medical students and professionals. Two strategies-designing learning environments with libraries of cases and creating opportunities for individualized teacher-guided training-should enable motivated individuals to acquire a full set of refined mental representations. Providing the right resources to support the expert-performance approach will allow such individuals to become self-regulated learners-that is, members of the medical community who have the tools to improve their own and their team members' performances throughout their entire professional careers.